Implementación de un sistema de costos y su incidencia en el aspecto económico financiero en la empresa industrial & comercial VU EIRL en el 2015 - Quispe Ulloa, Olga Jakeline (2017)
ABSTRACT The purpose of the work was to determine the incidence of the cost system in the company Industrial & Commercial V EIRL, for this was taken as population, the company and its sample was the size of the population, according to the test design was Non-experimental- Transversal, correlational type, as study material was used the observation and the documentary part. For the development has been used information taken directly from the reality, which has been analyzed, structured, and explained by reason of costs. As a result, the company uses a productive process but not the right one, although it is true that the company uses methods for product costing, its accountant considers that it lacks a cost system, just as the production engineer Is aware that the capacity of the machinery is only used 60% and this generates a reserve for idle capacity. It has been established that through the implementation of a cost system, it significantly influences the economic and financial aspect of the Industrial & Commercial VU EIRL company, in order to make the best decisions.